P53 mutations in gastric carcinomas. - Seruca, R. (Nature Publishing Group, 1992)
We carried out an immunohistochemical study and DNA analysis of 30 gastric carcinomas to evaluate p53 overexpression and allelic loss at 17p. The immunohistochemical study demonstrated immunoreactivity for p53 protein in four cases. Allelic loss for the pYNZ22.1 marker was detected in nine cases. In total, ten cases showed immunoreactivity for p53 protein, allelic loss, or both. The study of nine of these cases by constant denaturant gel electrophoresis revealed p53 mutations in three cases. We conclude that the prevalence of mutations of p53 in our series is similar to what has recently been observed in other cases of gastric cancer, but lower than in colon carcinomas. IMAGES: